Development of Science and Mathematics Teaching Modules Based on South Sumatra’s Natural Resources for Early Childhood Teachers - Waty, Evy Ratna Kartika; Syafar, Syafdaningsih; Hasmalena; Sofia, Ari; Ilhami, Akmillah; Pagarwati, Lia Dwi Ayu; Putri, Ayu Dwi; Marsya, Zechan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to develop a science and mathematics teaching module based on South Sumatra's natural resources and evaluate its validity and practicality. The research involved kindergarten teachers in Palembang and employed a Research and Development (R&D) approach using the Rowntree model, which includes three stages: needs analysis, product development, and evaluation. At the evaluation stage, Tessmer’s formative evaluation approach was applied, comprising self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Media and material experts conducted the expert review, while teachers and children participated in the one-to-one and small group evaluations. Data were collected through observation, documentation, questionnaires, and tests. The results indicated that the developed module was highly valid (96.09%) and practical, as evidenced by high implementation and effectiveness scores from both teachers and children. These findings suggest that the module can serve as a valuable resource for early childhood educators in teaching science and mathematics using local natural resources.